The role of Teratak Fitrah in promoting dialogue of life in Sabah - Khadijah Mohd. Hambali Suraya Sintang, Nurhanisah Senin dan Su; Suraya Sintang; Nurhanisah Senin; Suhaida Shaharud-din (IDOSI Publications, 2013)
This paper discusses the role of Teratak Fitrah Centre as a religious as well as social body and education centre to correlate the relationship and strengthening the brotherhood and Muslim community either those who are Muislims through conversion process or those who are originally Muslim by birth.